Linking operation plans to business objectives using QFD. (2nd January 2019) - Dror, Shuki
Abstract : Selection of appropriate operation plans is an essential, but complex task as it requires an understanding of their implications for the strategic objectives in a given industrial situation. This work utilised the quality function deployment method as an instrument for ranking operation plans of an individual organisation in terms of its business objectives. Two methodological stages are suggested. In the first stage, a 'house of strategy' matrix translates the improvement needs of a company's objectives into a list of competitive priority measures ranked according to their relative importance. A mean square error (MSE) criterion supporting the selection of vital competitive priorities to be improved is employed. In the second stage, each vital competitive priority is broken down into its relevant processes scenarios and an operation matrix is constructed to translate the desired improvement in the processes scenarios into a list of operation plans ranked by importance. Again, the MSE criterion supporting the selection of vital operation plans. In the construction of the operation matrix, it is assumed that synergy between the operation plans might be changed for each process scenario, that is, several roofs, corresponding to the number of rows in the operation matrix.